Analysis of Norm Conflict Between Law Number 11 of 2022 Concerning Sports and the Regulation of the Minister of Youth and Sports Number 14 of 2024 Concerning Management Standards for Sports Organizations within the Scope of Achievement Sports - Denial Ikram; I Made Sri Undy Mahardika; Heppy Hyma Puspytasar (Indonesian Journal of Sports Law, 2025)
This research analyzes the norm conflict between Law Number 11 of 2022 concerning Sports (Law 11/2022) and the Regulation of the Minister of Youth and Sports Number 14 of 2024 concerning Management Standards for Sports Organizations within the Scope of Achievement Sports (Permenpora No. 14 of 2024). The main objective is to identify potential normative contradictions and their implications for the autonomy and governance of achievement sports organizations in Indonesia. The analysis finds that a number of provisions in Permenpora No. 14 of 2024, such as the requirement for ministerial recommendations/approvals for internal organizational processes (congresses, changes to statutes/bylaws, legal entity ratification, changes in management), the minister's authority to intervene in internal disputes and form transition teams, and the establishment of detailed management criteria, potentially conflict with the principle of independence for sports organizations mandated by Law 11/2022. By applying the principle of lex superior derogat legi inferiori, it is concluded that the provisions of Permenpora No. 14 of 2024 that contradict Law 11/2022 are juridically null and void by law. This norm conflict has implications for the erosion of sports organizations' autonomy, the risk of excessive government intervention, legal uncertainty, and potential misalignment with international sports governance principles. It is recommended that Permenpora No. 14 of 2024 be comprehensively reviewed and revised to align with Law 11/2022, to ensure that management standards strengthen good governance without sacrificing the fundamental independence of sports organizations.